A new methodological approach for simulating water deficit in soybean genotypes. (2nd September 2021) - do Nascimento, Heloisa Rocha; Moura, Lorena de Oliveira; Duarte, Anunciene Barbosa; Dantas, Stênio Andrey Guedes; Ferreira, Dalton de Oliveira; Rosmaninho, Lucas Barbosa de Castro; Cavallin, Isabella Cristina; da Cunha, Fernando França; da Silva, Felipe Lopes
Abstract: Methodologies for imposing stress and reproducible results are a bottleneck for breeding programmes, and this is due to the lack of consensus between the existing methodologies. The aim of the present study was to propose and validate a new methodology for imposing water deficit in soybean that allows the identification of water deficit‐tolerant genotypes, at different harvest times and phenological stages. The methodology was based on the construction of a water retention curve in the soil to determine the water stresses that indicate the field capacity and the permanent wilt point and, thus, define the water regime in the conditions of control and stress. Seven trials were carried out to validate the methodology. In trials 1, 2, 3, 4, 5 and 6, the water deficit was imposed in the reproductive phase and the components of production were evaluated. In addition to these variables, leaf water potential was evaluated in trial 6. In trial 7, the plants were subjected to water deficit in the vegetative phase and the morphological traits were evaluated. The efficiency of the methodology was confirmed by the distinction between the conditions of control and stress, affirmed by the statistical differences in most of the traits evaluated in the reproductive and vegetative phases.